One‐Pot Fabrication of RGO–Ag3VO4 Nanocomposites by in situ Photoreduction using Different Sacrificial Agents: High Selectivity Toward Catechol Synthesis and Photodegradation Ability. (18th October 2013) - Das, Dipti P.; Samal, Alaka; Das, Jasobanta; Dash, Ajit; Gupta, Hariom
Abstract Weak photon absorption and fast carrier kinetics in graphene restrict its applications in photosensitive reactions. Such restrictions/limitations can be overcome by covalent coupling of another photosensitive nanostructure to graphene, forming graphene‐semiconductor nanocomposites. Herein, we report one‐pot synthesis of RGO–Ag3VO4 nanocomposites using various sacrificial agents like ethanol, methanol, propanol and ethylene glycol (EG) under visible light illumination. The Raman spectral analysis and 13C MAS NMR suggest ethanol to be the best sacrificial agent among those studied. Thermal analysis studies, further, confirm the stability of the synthesized nanocomposite with ethanol as sacrificial agent. In view of this, the activity toward dye degradation was focused over the composites prepared via ethanol as sacrificial agent. It was observed and proved that cationic dyes could be degraded quantitatively and swiftly compared to anionic dyes (37.79%) in 1.5 h. This suggests that the surface of the nanocomposites is anionic as partial reduction takes place during synthesis process. In case of mixed dye degradation process, it was noticed that the presence of cationic dye doubles the degradation of anionic dye. The activity of these synthesized nanocomposites is more than five‐fold toward the phototransformation of phenol and photodegradation of textile dyes under visible light illumination.